2020
DOI: 10.3389/fpsyg.2020.00044
|View full text |Cite
|
Sign up to set email alerts
|

Rejection Sensitivity, Self-Compassion, and Aggressive Behavior: The Role of Borderline Features as a Mediator

Abstract: This study used mediation analyses to examine the assumption that the presence of borderline personality features mediates the relationship between rejection sensitivity (RS), self-compassion, and aggressive behavior. Sixty adults consisting of 31 participants diagnosed with borderline personality disorder and 29 participants with no diagnosis of borderline personality disorder were assessed for RS, self-compassion, aggressive behavior, and borderline personality features. Mediation was found for the total agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…This mediating effect that we found suggests that self-compassion is associated with decreased rejection sensitivity, which translates into a lower level of loneliness. This result is in line with previous studies, which showed a relationship between self-compassion and rejection sensitivity (Sommerfeld & Shechory Bitton, 2020;Watson & Nesdale, 2012), and with studies pointing to rejection sensitivity as a risk factor for loneliness (Gao et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This mediating effect that we found suggests that self-compassion is associated with decreased rejection sensitivity, which translates into a lower level of loneliness. This result is in line with previous studies, which showed a relationship between self-compassion and rejection sensitivity (Sommerfeld & Shechory Bitton, 2020;Watson & Nesdale, 2012), and with studies pointing to rejection sensitivity as a risk factor for loneliness (Gao et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, we ran a Monte Carlo power analysis for mediation models using Schoemann et al's (2017) algorithm. Based on the results of previous studies, we expected moderate correlations between self‐compassion and loneliness (Liu et al, 2020) and high correlations between rejection sensitivity and both self‐compassion and loneliness (Sommerfeld & Shechory Bitton, 2020; Watson & Nesdale, 2012). The results suggested that, with an alpha of .05 and a power of .95, a sample of 81–84 participants was needed to detect effects of the predicted size.…”
Section: Methodsmentioning
confidence: 91%
“…This is a crucial future direction as prior experimental and sociological studies have found reliable gender differences in self‐reported and actual peer‐based aggressive behavior, especially in adolescence (Bettencourt & Kernahan, 1997; Björkqvist, 2018; Card et al, 2008; Harrendorf et al, 2010; Österman et al, 1998). Additionally, we were unable to test for the moderating effects of trait‐related differences known to influence rejection‐elicited aggression, such as self‐esteem (Kirkpatrick et al, 2002), narcissism (Twenge & Campbell, 2003), and rejection sensitivity (Ayduk et al, 1999, 2008; Sommerfeld & Shechory‐Bitton, 2020). Therefore, future studies should test if personality traits and susceptibility to rejection moderate the effects of rejection on aggressive/prosocial behavior.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] According to the suggested model in this study, the mediating influence of self-compassion seems to lower aggression levels among youth and may impact their psychological well-being positively. [ 37 38 ] This implies that when individuals begin lessening their online/offline divide, become mindful during online activities, feel connected to other humans and commence focus on self-care, then they may be able to restrain their overtly aggressive online behavior, such as, cyberbullying raucous commenting, trolling or cyber stalking; and consequently improve their mental health. [ 11 36 39 ]…”
Section: Discussionmentioning
confidence: 99%